2016
DOI: 10.1002/jsfa.7886
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant capacity of açaí (Euterpe oleracea) genotypes and commercial pulps

Abstract: The commercial samples showed higher antioxidant capacity and higher levels of anthocyanins and non-anthocyanic compounds than those of the genotype samples. Among the genotypes studied, L4P16 stood out for its higher contents of fibre and bioactive compounds and higher antioxidant capacity, indicating that this genotype has great potential for use in plant breeding programs that should be further explored. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 47 publications
5
18
0
3
Order By: Relevance
“…It was noted that almost half of the dried matter was composed of lipids (47.59%), which makes the açai pulp a food of high energetic value. The results of protein, lipid, and ash determination agree with the findings reported by Tonon et al [7] and Carvalho et al [30]. However, the amounts of digestible carbohydrates and fiber are discordant between our study and the previous two.…”
Section: Açai Compositionsupporting
confidence: 91%
“…It was noted that almost half of the dried matter was composed of lipids (47.59%), which makes the açai pulp a food of high energetic value. The results of protein, lipid, and ash determination agree with the findings reported by Tonon et al [7] and Carvalho et al [30]. However, the amounts of digestible carbohydrates and fiber are discordant between our study and the previous two.…”
Section: Açai Compositionsupporting
confidence: 91%
“…Data showed that cyanidin-3- O -glucoside is the major anthocyanin. These findings agreed with those of previous studies that also found that cyanidin-3- O -glucoside was the major anthocyanin found in the acai extracts [ 12 , 13 ]. Results also showed that independent of the concentration of the acai dye, the anthocyanin concentration was similar ( Table 3 ), and this result is probably because we employed the same prime material.…”
Section: Discussionsupporting
confidence: 93%
“…The principal flavonoid responsible for this anti-inflammatory activity is the flavone velutin [12]. Açaí fruit is also composed by high content of polyphenolic compounds, especially anthocyanins, as major components cyanidin-3-glucoside and cyanidin-3-rutinoside, and phenolic acids [13,14,15]. Açaí is commonly sold as dehydrated powder to be added to food, in dietary supplements or beverages.…”
Section: Introductionmentioning
confidence: 99%